Feminist Pedagogies: The Textuality of the Racialized Body in the Feminist Classroom - Lawson, Erica (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
This paper addresses two central questions: What are the challenges of practising feminist pedagogies in an increasingly market-driven and demanding educational climate? And how does a racialized instructor negotiate these challenges? These questions are examined from the perspective of a Black female professor who teaches Introduction to Women’s Studies and Feminist Theory to first- and second-year students, respectively.